The Influence of the Level of Financial Literacy and Digital Literacy on Generation Z's Interest in Saving at Bank Muamalat Indonesia KCP Mojokerto - Ardiansyah, Norick; Lesmana, Ceta Indra (Danadyaksa: Post Modern Economy Journal, 2024)
This research aims to determine the influence of financial literacy and digital literacy levels on Generation Z's interest in saving at Bank Muamalat Indonesia KCP Mojokerto. This research uses quantitative methods using primary data. The population of this research is Generation Z customers who save at Bank Muamalat Indonesia KCP Mojokerto. Data collection was carried out by distributing questionnaires to customers in the city of Mojokerto as many as 96 sample respondents using a purposive sampling technique with the following considerations: (1) generation Z customers who save at Bank Muamalat Indonesia KCP Mojokerto. The data obtained was then processed using the multiple linear regression method using IBM SPSS 25 software. The analysis used included validity and reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. The results of this research show that partially financial literacy has a positive and significant effect on Generation Z's interest in saving at Bank Muamalat Indonesia KCP Mojokerto, digital literacy has a positive and significant effect on Generation Z's interest in saving at Bank Muamalat Indonesia KCP Mojokerto. Simultaneously financial literacy and digital literacy influence Generation Z's interest in saving at Bank Muamalat Indonesia KCP Mojokerto.